Thoracolumbar Vertebral Injuries with Neurological Deficit Treated with Posterior Decompression, Short Segment Pedicle Screw Fixation, and Interlaminar Fusion - Sachin Kumar; Satish Kumar; Rajender Kumar Arya; Avinash Kumar (Asian Spine Journal, 2017)
Study DesignProspective clinical study.PurposeThe purpose of this study was to evaluate the effect of interlaminar fusion and short segment pedicle screw fixation on thoracolumbar vertebral injuries for preventing pain and post-traumatic kyphosis.Overview of LiteratureThe treatment of thoracolumbar injuries continues to be one of the most controversial areas in spine care. The main aim of surgical treatment is to decompress the spinal cord or nerve roots, realign the spine, and correct or prevent post-traumatic kyphosis. We evaluated the outcome of interlaminar fusion along with posterior decompression and short segment pedicle screw fixation in patients with thoracolumbar fractures with neurological deficit.MethodsTwenty-two patients with traumatic thoracolumbar vertebral injuries and neurological deficit underwent short segment pedicle screw fixation above and below the fractured vertebrae, posterior decompression, and interlaminar fusion using a bone graft.ResultsAll patients were followed up for 12 months postoperatively. The average operative time and blood loss was 142 minutes and 214 mL, respectively. Of the 22 patients, 14 recovered completely. Of the nine patients with American Spinal Injury Association (ASIA) grade A disease, two improved by 1 grade, whereas one each improved by grades 2, 3, and 4, and four did not recover. Radiologically, vertebral kyphosis angle improved from 20.91 preoperatively to 15.73 postoperatively, sagittal index improved from 24.77 to 18.73, the sagittal plane kyphosis angle improved from 17.45 to 11.41, regional angle kyphosis improved from 14.73 to 10.14, the superior inferior end plate angle from 16.14 to 13.00, and mean anterior body compression improved from 36.26 to 27.64 postoperatively. No implant failed and no patient had neurological deterioration.ConclusionsShort segment pedicle screw fixation with posterior decompression and interlaminar fusion provided considerable reduction in kyphosis, restored the vertebral height of patients with thoracolumbar vertebral injuries and neurological deficit, and prevented development of delayed kyphotic deformity.